Republic of Kosovo : First Review Under the Stand-By Arrangement, and Request for Modification of Performance Criteria: Staff Report; Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper presents findings of the First Review Under the Stand-By Arrangement (SBA) for the Republic of Kosovo. The paper highlights that macroeconomic and financial policies are broadly on-track. All end-April and continuous quantitative performance criteria under the SBA were met with comfortable margins, as a modest shortfall in revenue collection was overcompensated by underexecution of spending. The program's key objectives remain restoring a sustainable fiscal position and sufficient government cash buffers, anchoring fiscal policy through the introduction of a fiscal rule, and enhancing the resilience of the financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet